Integrative Metagenomics–Metabolomics for Analyzing the Relationship Between Microorganisms and Non-volatile Profiles of Traditional Xiaoqu - Zhao, Chi; Su, Wei; Mu, Yu; Mu, Yingchun; Jiang, Li (Frontiers in Microbiology, 2021)
Xiaoqu, one of the three traditional jiuqu in China, is a saccharifying and fermenting agent used in Xiaoqu jiu brewing, with different composition of ingredients and crafting preparation in various regions. The yield and quality of Xiaoqu jiu are significantly affected by the metabolites and microbiota of Xiaoqu; however, the relationship between them remains poorly understood. This work aimed to analyze the relationship between the microbiota and metabolites in 3 typical traditional Xiaoqu from the Guizhou province, China. The nonvolatile metabolites of Xiaoqu were detected using gas chromatography time of flight mass spectrometry, whereas the classification and metabolic potential of its microbiota were studied using metagenomic sequencing. Results showed that Firmicutes, Proteobacteria, and Ascomycota were the dominant phyla, while Lactobacillus, Bacillus, Acinetobacter, Leuconostoc, Saccharomyces, Weissella, and Aspergillus were the predominant genera. Functional annotation revealed a major association with the metabolism of carbohydrates, cofactors and vitamins, and amino acids. In total, 39 metabolites were identified as significantly different metabolites (SDMs), and pathway analysis demonstrated that these SDMs were involved in 47 metabolic pathways, primarily in the metabolism of starch and sucrose; glycine, serine, and threonine; glyoxylate and dicarboxylate; and pyruvate; and in the biosynthesis of pantothenate and CoA. Further, based on Spearman's correlation analysis, Aspergillus, Saccharomyces, Lactobacillus, Acetobacter, Weissella, Pantoea, Desmospora, and Bacillus were closely related to the production of physicochemical indexes and SDMs. Moreover, we constructed a metabolic network for the breakdown of substrates and formation of SDMs in Xiaoqu, which was primarily composed of the metabolism of carbohydrates and the TCA cycle. These results are conducive in comprehending the functional microorganisms and the metabolic patterns in the traditional Guizhou Xiaoqu, and might guide researchers in the production of stable and efficient Xiaoqu in the future.